Pengembangan Kompetensi Pedagogik Guru PAI - Binti Ngaliyah; Agus Joko Purwanto (Jurnal Wahana Literasi Pendidikan, 2026)
This study attempts to describe and analyze the development of PAI teachers' pedagogical competencies. The method used in this study is qualitative, using a literature review approach (library research). The purpose of developing PAI teachers' pedagogical competencies is to develop teacher professionalism, which includes pedagogical competencies that can improve the quality of learning to be more active, innovative, creative, and enjoyable so that learning objectives can be achieved. The competencies specified in the Law on Teachers and Lecturers must meet four requirements, namely pedagogical competence, professional competence, personal competence, and social competence. However, the government is only able to test two competencies, namely pedagogical competence and professional competence. This is because these aspects are considered the most fundamental and essential aspects that teaching and education personnel must possess. By focusing on these two main competencies, the competency testing process becomes more effective in terms of time and can be implemented in a more structured manner that can be measured nationally.